“LET’S MOVE!” CAMPAIGN: EDUCATION AND STIMULATION OF PHYSICAL EXERCISE IN OLDER ADULTS - Sundari Indah Wiyasihati; Hayuris Kinandita Setiawan; Purwo Sri Rejeki; Irfiansyah Irwadi (Universitas Airlangga, 2023)
The increase in human life expectancy has led to an increase in the number of older adults worldwide, including in Indonesia. The aging population raises sarcopenia as a further problem in geriatric medicine. Sarcopenia is a syndrome characterized by progressive skeletal muscle mass and strength loss. This syndrome is associated with reduced quality of life, increased risk of falls, and even death. Physical exercise is the only effective intervention strategy. Therefore, we designed this community service program for socializing the healthy lifestyle of the elderly with one focus on physical exercise as a promotive, preventive, and curative effort on the incidence of sarcopenia in the elderly. The method chosen was socialization and educating fifty-two pre-elderly and elderly target partners regarding the healthy lifestyle for the older adults and elderly exercise activities as stimulation. The